Which Vehicle To Select? - Fawaz, Wissam F. (2012)
In wireless networking, an Opportunistic Bundle Release Mechanism (OBRM) is a data bundle forwarding mechanism characterized by its ability to operate over Intermittently Connected Networks (ICNs) where end-to-end paths are not continuously available. Known for their intrinsic connectivity intermittence, vehicular networks constitute an ideal recreation ground for OBRMs. This letter, proposes the Optimal Vehicle Selection OBRM (OVS-OBRM) with the objective of minimizing the average bundle delivery delay.